Does Location Matter In Gender Equality? The Impact Of Location On Religious And Cultural Ideologies, Sex Role Preferences And Division Of Labour Among Sikh Couples In Malaysia - Parveen, Kaur (Publications International, 2019)
This study looks at the role of location in influencing the religious and cultural ideologies and sex-role preferences, and the pattern of division of labour of the Sikh community in Malaysia. The respondents were selected from metropolitan, urban and rural areas in Perak, Malaysia. The diverse locations are vital in understanding the possible effects of these different environments on the religious and cultural ideologies, sex-role preferences and division of labour of the communities. The different locations were used to measure the effect of different levels of development on gender ideology, sex-role perceptions and practices in their household division of labour. Thus this study takes into account development through its proxy location, in its examination of the above aspects of the Sikh community.